The RELATIONSHIP BETWEEN MATERNAL AGE AND INTRAUTERINE GROWTH RESTRICTION (IUGR) AT DR. MOEWARDI GENERAL HOSPITAL, SURAKARTA - Khusniyatin Dwi Nabiilah; Dwi Hidayah; Dewinda Candrarukmi (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2025)
Background. Intrauterine Growth Restriction (IUGR) is a fetal growth disorder that significantly impacts neonatal morbidity and mortality, with a high incidence, especially in developing countries. Maternal age is known to be a major risk factor associated with IUGR, therefore, research on the relationship between gestational age and IUGR is crucial to support more effective prevention and treatment efforts in Indonesia. The aim of this study was to determine the relationship between maternal age and IUGR at Dr. Moewardi Regional General Hospital. Methods. This study employed a cross-sectional approach. Sixty-seven pregnant women, selected based on inclusion and exclusion criteria, whose deliveries took place at Dr. Moewardi Regional Hospital between January and December 2024, participated in this study. Secondary data were obtained from medical records and then analyzed using chi-square and logistic regression tests. The Result of 67 subjects, 35 (52.2%) delivered babies with IUGR and 32 (47.8%) non-IUGR[3]. Mothers with risk age had 14.286 times higher odds of delivering babies with IUGR compared to non-risk age (OR 14.286; 95% CI 4.397–46.413; p=0.000). Risk interpregnancy interval also showed significant association with IUGR (OR 12.632; 95% CI 2.606–61.222; p=0.000). Parity, nutritional status, and comorbidities did not show significant association with IUGR. Conclusion: Maternal age is significantly related to IUGR incidence. Pregnant women with risk age require more intensive antenatal monitoring to detect fetal growth disorders early.